Kajian Tentang Hukum Kehutanan Terhadap Daerah Otonom Baru (DOB) Di Indonesia - Warsito Warsito; Rahayu Subekti (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
By laying a foundation in the forestry environment as a basis for running a regional government system, it will encourage the ability to reduce aspects of forest destruction in the region. The deterioration of existing forest conditions cannot be separated from the existence of a development and licensing system that has not prioritized forestry aspects as aspects that need to be prioritized. The effectiveness of law regarding human environmental issues cannot be separated from the state of the administrative apparatus and law enforcement officials as the infrastructure for effective implementation of the law in the realities of environmental life.